(untitled) (Journal of Hama University, 2024)
This research seeks to study the style of calling in the poetry of abi al-atahiya, an applied rhetorical study that fulfills the intended purpose. The research began with defining the appeal linguistically and idiomatically, then mentioning the rhetorical and metaphorical meanings that the appeal came to in the poet, through analyzing the appropriate poetic evidence with the use of the methods of the appeal inadeep semantic manner expressing the latents of the human self. The research was concluded with accurate scientific results reached by the study.